Strategi Pengelolaan Pariwisata Bintan di Era Kenormalan Baru - Prambudi, Yogi; Mutiarin, Dyah (Jurnal Ilmiah Pariwisata, 2022)
Tourism has a significant contribution to the development of an area. Optimization of tourism management in this area needs to be implemented immediately so that useful values can be obtained while these factors can be well maintained. The purpose of this research is to knowing how the management strategy about tourism in new normal situation at Bintan Region. This research. This research using the SWOT analyses to evaluate the strength, weakness, opportunity, and threat. Using SWOT analyses can be a tools to formulating the policy, especially during the crisis situation. The technic method of this research is qualitative approach. Which the paper is using depth analysing with the main variable of the data, beside that this research is evaluate by the secondary data. The result of this paper is the term "new normalcy" refers to the process of rediscovering new standards and ideals through critical thinking processes triggered by crucial occurrences.several indicators are used when developing and formulating tourism strategies in Bintan. These indicators include management models, improving service and security standards, social influences, developing models of environmental activities in tourism areas, and conducting survey visits. at a Bintan tourism spot. Keywords: Pandemic Covid-19, New Normal Era, SWOT Analysis